2018
DOI: 10.3390/en11123418
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Economic and Resilience-Based Optimization for Disaster Recovery Management of Critical Infrastructures

Abstract: The traditional grid operation is unfortunately lacking the resilience and responsiveness in reacting to contingency events due to the poor utilization of available resources in mitigating the shortfalls. Such an unaddressed issue may affect the grid stability and the ultimate grid blackout. Therefore, this paper models a grid optimization module consisting of a mid and low (microgrid) voltage level grid component of an urban grid network for a disaster recovery. The model minimizes the cost of generation requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…The constant flux of information and services must be assured (Yuan et al , 2021; Cimellaro et al , 2016). For example, implementing new technologies such as blockchain to protect and ensure connectivity on CIs linked through the internet of things devices (Fekete and Rhyner, 2020; Bellini et al , 2020; Lau et al , 2018; Demertzis et al , 2020). The “Social” category consists of indicators related to building resilience of CIs through education and professional development courses.…”
Section: Resultsmentioning
confidence: 99%
“…The constant flux of information and services must be assured (Yuan et al , 2021; Cimellaro et al , 2016). For example, implementing new technologies such as blockchain to protect and ensure connectivity on CIs linked through the internet of things devices (Fekete and Rhyner, 2020; Bellini et al , 2020; Lau et al , 2018; Demertzis et al , 2020). The “Social” category consists of indicators related to building resilience of CIs through education and professional development courses.…”
Section: Resultsmentioning
confidence: 99%
“…Vadali et al [51] proposed the optimal approach to maintaining infrastructure resilience by using a bi-national dynamic traffic assignment model; this model provides a timely insight into the daily travel impact and economic cost of an unexpected disruption to the ports-of-entry infrastructure. Lau et al [52] identified the most efficient approach to meeting the demand shortage of critical infrastructure and maintaining the resilience of the power grid by establishing a grid optimization model, which consisted of the low-level (micro-grid) and mid-level voltage grid components in urban power grids for disaster recovery.…”
Section: Assessment Of Infrastructure Resiliencementioning
confidence: 99%
“…The results are illustrated in Figure 7. According to the results, among the surveyed studies, energy systems (e.g., [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]), transportation networks (e.g., [56][57][58][59][60][61][62][63][64][65][66][67][68][69]), and water supply networks (e.g., [70][71][72][73][74][75][76][77][78]) have the highest frequency as case studies, among other fields. Meanwhile, health care infrastructures [79,80], industrial processes [81][82][83], supply chain [84], mining sector…”
Section: In What Type Of Technological Ciss Has the Concept Of Resilience Been Used?mentioning
confidence: 99%